Handbook of meat and meat processing - Hui, Y. H. (Yiu H.) (Boca Raton, Fla. : CRC Press, 2012)
"Preface The consumption of red meat and meat products has a long history in most cultures. Meat is a source of nutrients, as well as a sign of wealth in some countries. Various techniques have been developed in different parts of the world over the centuries to preserve meat for extended shelf life and enjoyment. Even nonedible parts of animals are used for various reasons. Thus, meat, meat products, and by-products are important to our daily life. In the past three decades, many books on the science and technology of meats and meat products have been published. Many of these books are useful reference texts and well received by professionals in the meat industries, academia, and the government. Meat Science and Applications is one such example. It was published in 2001 by the then Marcel Dekker of New York. A decade later, the current publisher, CRC Press, is releasing a second edition of the book with a new title Handbook of Meat and Meat Processing. The change in title reflects the expansion of coverage in depth and breadth from the first edition, as illustrated in the table of contents of this book. Apart from updating materials in the first edition, the new edition contains 51 chapters instead of 27. This second edition is divided into six parts. Part I covers an overview of the meat processing industries in the United States followed by chapters on muscle biology, meat composition, and chemistry. Part II covers meat attributes and characteristics such as color, flavor, and analyses. Part III describes the primary processing of meat, including antemortem and postmortem slaughter, carcass evaluation, religious status, and so on. Part IV discusses the principles and applications in the secondary processing of meat, for example, breading, curing, and fermentation"--
pt. 1. Meat industries -- pt. 2. Meat science -- pt. 3. Quality and other attributes -- pt. 4. Primary processing -- pt. 5. Secondary processing : principles and applications -- pt. 6. Secondary processing : products manufacturing -- pt. 7. Meat safety and workers safety.
Rev. ed. of: Meat science and applications / edited by Y.H. Hui ... [et al.]. 2001.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Meat; Meat industry and trade; Electronic books